The Pessimism of Thomas Hardy Towards Matrimony, Anglicanism, and Society: Exploring the Pessimistic Views of Thomas Hardy (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This research seeks to prove Thomas Hardy's pessimism by analyzing his biography andillustrating how three of his novelsFar from the Madding Crowd, Tess of the d'Urbervilles, and Jude theObscurereflect real-world events, relationships, and societal difficulties in Hardy's own life. ThomasHardy was an emotional author who admired strong, self-reliant women. Hardy's final work demonstrateshis keen awareness of the world at the end of the Victorian era, including the struggles of women as theyadapted from the traditional role of wives to that of new women and suffragette activists who challengedVictorian norms in their quest for equality and recognition. Hardy's pessimism had its origins in his earlyyears, when he realized that his existence was the consequence of an unwanted birth, and continuedthroughout his adolescence and young adulthood when he realized that his family could not afford toprovide him with a formal education. Hardy became more aware of the social divide between him andindividuals from more privileged backgrounds as he entered adulthood. When it came to imagining thefuture role of women in marriage and society, Hardy was decades ahead of his time.The hopelessstorylines of these three books were inspired by his hopeless relationships with two women his cousinTryphena Sparks and his first wife Emma Lavinia Gifford. Thomas Hardy, a writer and poet of thenineteenth century, became known as a gloomy figure due to his experiences in life, including the harshenvironment in which he lived, his lack of money, two terrible marriages, and the inability of his final twoworks to be accepted by his readers.